Spray Scheduling for Management of Foliar Diseases in Onion (Allium cepa L.) - Tripathy, P.; Sahoo, B. B.; Priyadarshini, A.; Patel, D.; Dash, D. K. (International Journal of Bio-resource and Stress Management, 2023)
Among the various foliar diseases affecting leaves and bulbs of onion, purple blotch incited by Alterrinari porri Ell (Ciferri), while thrips (Thrips tabaci Lindeman) among the insects are the most devastating and prevalent in India. The present investigation was conducted to study the spray scheduling for management of foliar diseases in onion during rabi season of 2010-11 to 2012-13 under AINRPOG, College of Horticulture(OUAT), Odisha, India in RBD with six treatments replicated four times. The spray schedule consists of combined spray of both broad spectrum and contact fungicides with or without insecticides in alternate fashion along with control. The results revealed significantly minimum disease incidence (74.26 ,68.17 and 65.01%), severity (54.25, 31.25 and 33.00%), thrips plant-1 (33.50, 17.79 and 19.68) , marketable bulb yield (19.58,13.75 and 15.66 t ha-1 ) and total bulb yield (27.95, 24.88 and 27.60 tha-1) were recorded with spray schedule of mancozeb @ 0.25%+methomyl @ 0.8 g l-1, tricyclazole @ 0.1%+carbosulfan @ 2 ml l-1 and Hexaconazole @0.1%+profenofos 1 ml l-1 at 30, 45 and 60 DAT (T4) during three consecutive years, respectively. The next best recommendation was application of mancozeb @ 0.25%+methomyl @ 0.8 g l-1, propiconazole @ 0.1%+carbosulfan @ 2 ml l-1 and copper oxychloride @ 0.25%+profenofos 1ml l-1 at 30, 45 and 60 DAT (T3) in onion. Thus, it may be concluded that, combined application of insecticides and fungicides not only reduces the incidence of foliar disease and thrips infestation but also increases bulb yield instead of their sole application during 30 to 60 DAT.